Efficacy of collagen peptide supplementation on bone and muscle health: a meta-analysis - Sun, Chongxiao; Yang, Ao; Teng, Fei; Xia, Yayi (Frontiers in Nutrition, 2025)
BackgroundCollagen peptide supplements, especially when combined with vitamin D as well as calcium, are showing promise as a means of enhancing the condition of muscle and bone. This meta-analysis examined how collagen peptide intake affected muscular performance, bone turnover metrics, probability of fracture, and bone mineral density (BMD).ObjectiveThe primary goal of this meta-analysis was to investigate the influence of collagen peptide treatment on musculoskeletal indices, bone turnover indicators, and BMD. The interaction of collagen peptides with vitamin D and calcium was of special significance.MethodsRandomized trials evaluating collagen peptide intake, either independently or in combination with calcium and vitamin D, were systematically reviewed and meta-analyzed. In order to synthesize effect sizes among trials, standardized mean differences (SMDs) using 95% confidence intervals were computed. The Cochran’s Q analysis and the I2 measure were employed to determine variability.ResultsStudies revealed that supplementing with collagen peptide significantly increased BMD in the femoral neck and spine. Nonetheless, there was a significant amount of variation in BMD results across trials (I2 = 80.1%). Collagen had no noticeable variance (I2 = 0%) and enhanced bone turnover indicators (SMD 0.40–0.58) and muscle performance (SMD 0.60 [0.05, 1.15]). When collagen was paired with the nutrients vitamin D and calcium, positive synergies were noticed (SMDs 0.40–0.56).ConclusionCollagen peptide supplementation, particularly when synergized with calcium and vitamin D, is associated with continuous improvements in BMD, bone turnover markers, and muscle function. All these variables are important for fracture prevention. Owing to the information collagen peptides could be used as an adjunct therapy for managing osteoporosis.